RTEL1 is upregulated in gastric cancer and promotes tumor growth - Chunyu Yang; Suzeng Wang; Ge Gao; Peiwen Xu; Mengyuan Qian; Yuan Yin; Surui Yao; Zhaohui Huang; Zehua Bian (Journal of Cancer Research and Clinical Oncology)
Abstract Gastric cancer (GC) is one of the most common cancers worldwide, with increasing incidence and mortality rates. It is typically diagnosed at advanced stages, leading to a poor prognosis. GC is a highly heterogeneous disease and its progression is associated with complex interplay between genetic and environmental factors. Identifying novel genes and pathways involved in GC development is crucial for improving the therapeutic outcome. Regulator of Telomerase Length 1 (RTEL1) has been found to maintain telomere stability through its helicase activity, facilitating telomere reconstruction and repair. However, the precise role of RTEL1 in human cancers, particularly in GC, is not yet fully understood. In this study, we observed significantly increased RTEL1 expression in GC tissues, which was associated with a poor prognosis. Functionally, RTEL1 promotes GC cell proliferation both in vitro and in vivo. Additionally, RTEL1 appears to regulate multiple signaling pathways, with a particular promoting effect on the cell cycle progression. Notably, CDC23 and TRIP13 are potential downstream target genes of RTEL1, which may mediate its tumor-promoting effects in GC. These findings suggest that RTEL1 plays a critical role in GC tumorigenesis and could be a promising target for the therapy and prognosis of GC.